PEMETAAN PEMBELAJARAN BIOLOGI BERBASIS SCIENTIFIC APPROACH DI SMA NEGERI 1 BINJAI - Ummu Rahmatika; Amrizal Amrizal (Universitas Negeri Medan, 2018)
This study aims to determine the implementation of biological learning based on scientific approach, learning activities based on scientific learning, the dominant activity in the application of scientific approach, and scientific learning stages which is a problem in biology learning in SMA Negeri 1 Binjai T.P.2016 / 2017. The research design used is descriptive quantitative by using survey method. The samples were 2 biology teachers and 114 students. Data collection techniques using, observation sheets, student questionnaires, and interview guidelines. The result of the analysis shows that the implementation of learning with scientific approach is 80% with the interpretation implemented sufficiently. While the learning phase activity observes, asks, tries, associates, and communicates it is 86%, 85%, 75%, 78%, 75% with average enough to do. The dominant scientific learning stage is observation, and the scientific learning stage which is a problem in learning that is asking, and collecting information.Keywords: learning activities of scientific approach, implementation of learning, learning activity.